Strengthening Housewives' Environmental Awareness to Reduce Plastic Use in Pulokerto Village - Diana Dewi Sartika; Dadang Hikmah Purnama; Gita Isyanawulan; Deska Fitriyani; Muhammad Rifai (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2026)
The use of single-use plastics has become a major environmental problem in many places, including the Pulokerto Village in Gandus District. Non-biodegradable plastic waste pollutes the environment, clogs waterways, and affects public health. Homemakers are a group in society who play an important role in managing household waste because of their strategic role in regulating consumption patterns and daily habits within the family. The service activity took the theme of strengthening environmental awareness among housewives to minimize plastic use. Identifying community needs shows that there is a lack of knowledge and awareness about environmental cleanliness due to plastic use. The potential in Pulokerto Village includes the central role of housewives, who hold a strategic position in leading groups; active social organizations, including active PKK groups, savings clubs, and health posts at Pulokerto Village; the spirit of mutual cooperation and environmental awareness among the community; and access to digital information and social media. Therefore, the solution offered is an educational lecture for the service participants, who are housewives. The implementation method uses a participatory approach. The innovation in this service activity is the Eco Challenge Family (Plastic-Free Home Competition), Reusable Bag (Simple Cloth Shopping Bag), and Plastic Exchange for Household Items. The program is community-based, involving RT/RW, and is designed to be simple and applicable in daily life, adapting to the needs and potential of the local community. Therefore, the expected outcomes of this service activity are short-term results, in the form of changes in the initial attitudes and behaviors of housewives, and long-term results, in the form of changes in the environment and a healthier and cleaner lifestyle.The results of the activity show an increase in housewives' knowledge from 50.8% (pre test) to 56.8% (post test), as well as the formation of three program innovations: Eco Challenge Family, Reusable Bag, and Plastic Exchange for Household Items.